1984
DOI: 10.1093/nar/12.20.7663
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mRNA primary and secondary structure on human IFN-γ gene expression inE. coli

Abstract: Parameters influencing the efficiency of expression of the human immune interferon (IFN-gamma) gene in E. coli were studied by comparing a series of eight in vitro-derived gene variants. These contained all possible combinations of silent mutations in the first three codons of the mature IFN-gamma polypeptide coding sequence. Expression levels varied up to 50-fold among the different constructions. Comparison of messenger RNA secondary structure models for each variant suggested that the presence of stem-loop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…pICI 0020 incorporates a trp leader (AAAAAGGGTATCGACAm) ribosome-binding site sequence [39]; pICI 0027 incorporates a bicistronic ribosome-binding site sequence [40] ; pICI 0029 incorporates a ribosome-binding sequence (ACACAGGAACAGATCTA, -TG) used to increase the expression of IFN-y in E. coli [41]. A full-length PAI-1 cDNA clone was isolated from the human placental cDNA library by screening with synthetic oligonucleotide probes with the sequences CAATCGCAAGG-CACCTCTGAGAACTTCCAGG and TCTCCAGTTTGTC-CCAGATGAAGGCGTG, which hybridize to the 5' and 3' ends, respectively, of the published sequence coding for P.41-1.…”
Section: General Dna Techniquesmentioning
confidence: 99%
“…pICI 0020 incorporates a trp leader (AAAAAGGGTATCGACAm) ribosome-binding site sequence [39]; pICI 0027 incorporates a bicistronic ribosome-binding site sequence [40] ; pICI 0029 incorporates a ribosome-binding sequence (ACACAGGAACAGATCTA, -TG) used to increase the expression of IFN-y in E. coli [41]. A full-length PAI-1 cDNA clone was isolated from the human placental cDNA library by screening with synthetic oligonucleotide probes with the sequences CAATCGCAAGG-CACCTCTGAGAACTTCCAGG and TCTCCAGTTTGTC-CCAGATGAAGGCGTG, which hybridize to the 5' and 3' ends, respectively, of the published sequence coding for P.41-1.…”
Section: General Dna Techniquesmentioning
confidence: 99%
“…More or less stable structures of the mRNA translation initiation region have been investigated (10,14,20). These studies, which focused on the ribosome binding site and its tendency to hybridize with nearby sequences, reported that such structures, if their free energy was weaker than ±6 kcal/mol, did not affect the ribosome.…”
Section: Introductionmentioning
confidence: 99%
“…The complete coding sequence of mPAI-2 was placed under the control of the A PL promoter in the vector pLK58 (27) with a synthetic oligonucleotide inserted upstream of the ATG to provide a bacterial ribosome binding site at an appropriate distance from the start codon (28), giving the plasmid pBTA447. Cell extracts of induced E. coli N4830 containing pBTA447 showed biologically active mPAI-2, as evidenced by the shift in electrophoretic mobility in the presence of urokinase, characteristic of the formation of a urokinase-mPAI-2 complex (Fig.…”
Section: Resultsmentioning
confidence: 99%